Applying Performance Management in Public Apparatus Development at Regional Level - Yunus, Muhammad; Mujahid, Faiz; Atmansyah, Lutfi; Edy, Nelman; Yani, Andi Ahmad (Departemen Ilmu Administrasi FISIP UNHAS, 2022)
This study aims to analyze the performance of officials in the management of conservation areas at the Agency of Natural Resources Conservation Center (NRCC) of South Sulawesi Province. The study applies a qualitative descriptive approach and data were collected through interviews and document studies. The results of the study indicate that the implementation of performance management in the NRCC of South Sulawesi has not been optimal. This is due to the limited number of employees, a lack of training and education and problems in the management of conservation areas. However, the performance management process at the NRCC has been organasied consistently, starting from performance planning, performance implementation and performance evaluation.